A Randomized Prospective Study of Prophylactic Cloxacillin in Breast Reduction Surgery. Issue 1 (January 2015) - Lewin, Richard; Elander, Anna; Thorarinsson, Andri; Kölby, Lars; Sahlin, Per-Erik; Lundberg, Jonas; Panczel, Alexander; Lidén, Mattias
Abstract : Background: Postoperative infection after breast reduction surgery is a common complication, with the most commonly involved pathogen being Staphylococcus aureus . Previous studies of antibiotic prophylaxis in breast reduction surgery have been inconclusive. The aim of the present study was to clarify the role of prophylactic antibiotics in breast reduction surgery. Methods: In total, 325 women were randomized to antibiotic prophylaxis [with 2 g of cloxacillin intravenously (IV) or 600 mg of clindamycin IV] (intervention group) or no antibiotic prophylaxis (control group). Follow-up was conducted at 1 and 2 weeks postoperatively. Patients with signs of infections or other complications were followed up until resolution. Patients who received antibiotic treatment within 30 days from surgery (cloxacillin 750 mg or clindamycin 300 mg orally) were considered having an infection and this was the main outcome variable. All postoperative infections were also judged according to a graded scale. Results: In the intervention group, 26 (16.0%) patients were treated with antibiotic; and in the control group, 32 (19.6%) patients were treated with antibiotics. No difference was found between the groups (relative risk, 0.82; 95% confidence interval, 0.51–1.31; P = 0.49). Twenty-two (14%) patients in the intervention group were classified to have a possible infection according to the scale compared to 27 (17%) in the control group. No statistical difference was found (relative risk, 0.81; 95% confidence interval, 0.48–1.37; P = 0.54). Conclusions: Prophylactic cloxacillin as a single-dose IV in breast reduction surgery does not reduce the incidence of postoperative infections.